Crime and the rise of modern America: a history from 1865 - 1941 - Allerfeldt, Kristofer (Routledge, 2011)
The crimes of the century -- Crime and the West -- Hate crime -- Policing and imprisonment -- Conmen, swindlers, and dupes -- Business and financial crime -- Prohibitions -- Sex crime -- Political crime : scandal, sleaze and corruption -- Terrorists : rebels, radicals and freedom fighters and criminals with a cause -- Immigration and crime